Basic theory, recent history and preliminary economics of three-phase AC plasma reactor/furnaces - W. G. Brown (Canadian Institute of Mining, Metallurgy and Petroleum, 1991)
"Review of prototype testing of two types of three-phase, argon stabilized reactor/furnace indicates specialized advantages for both, as compared with existing metallurgical furnace technology. They are: the direct-arc, plasma-torch furnace (Knipp); and the indirect, plasma extended-arc reactor (PEAR), developed at the University of Toronto.IntroductionA unique type of three-phase AC, plasma extended-arc reactor, (PEAR), shown in Figure la with gravity feed, has been undergoing development at the University of Toronto, during the past fifteen years: argon gas, introduced axially through drilled-holes in ordinary graphite electrodes, increases the length of indirect arcing and improves electrical stability while decreasing electrode consumption as compared with the performance of AC electric arc furnaces (EAF 's). Meanwhile and independently, a three-phase, transferred arc plasma furnace (Fig. 1b) has been developed by the Krupp Research Institute in Germany, using argon-stabilized, water- cooled plasma-torches with thoriated tungsten electrodes.Accordingly, the two types of furnace are similar as to both three phase and stabilized operation, but otherwise they differ in several respects, ranging from indirect versus direct-arcing to principal intended application and current state of practical development. Between them they raise questions: (I) of their present or fore seeable economics in comparison with existing processes they are intended to replace , (see Heinke and Neuschutz, 1986, for a review of the merit s of AC and DC plasma-torch furnaces); and (2) of the state of development and accessibility of their plasma theory-in-common."